Reporting guideline and clinical trial registration requirements in gastroenterology and hepatology journals. Issue 2 (June 2018) - Jorski, Austin; Scott, Jared; Heavener, Trace; Vassar, Matt
ABSTRACT: Aim: The objective of this study was to evaluate the current recommendations and requirements of gastroenterology and hepatology journals concerning reporting guidelines and clinical trial registration. Current research on the topic is sparse and in need of further research in both clinical trial registration and guideline adherence. Methods: The authors performed a review of journal protocols and 'Instructions for Authors' regarding guideline adherence and trial registration requirements within 30 gastroenterology and hepatology journals. We searched the Expanded Science Citation Index of the 2015 Journal Citation Reports to determine if each journal required, recommended, or made no mention of 17 guidelines and clinical trial registration. Results: A majority (23/30; 76.7%) of the journals either required or recommended reporting guideline usage, whereas the remainder (7/30; 23.3%) had no such policy. In addition, 14 (14/30; 46.7%) require or recommend trial registration. Journals with a higher impact factor were associated with greater reporting guideline adherence ( r pb  = 0.43, P  < 0.05). There was not a significant relationship between journal impact factor and trial registration requirements ( r pb  = 0.16, P  > 0.05). Consolidated Standards of Reporting Trials was the most often required guideline (9/30; 30%), whereas Animal Research: Reporting of In Vivo Experiments and Preferred Reporting Items for Systematic Reviews and Meta-Analyses were tied for second most often required (6/30 each; 20% each). Clinical trial registration was most common via ClinicalTrials.gov (9/30; 30%). Conclusion: A majority of gastroenterology or hepatology journals either require or recommend reporting guideline usage, but just less than one-half of the journals did the same for trial registration. Abstract : Supplemental Digital Content is available in the text